Improved Benefit Risk Profile of Rivaroxaban in a Subpopulation of the MAGELLAN Study. (19th November 2019) - Spyropoulos, Alex C.; Lipardi, Concetta; Xu, Jianfeng; Lu, Wentao; Suh, Eunyoung; Yuan, Zhong; Levitan, Bennett; Sugarmann, Chiara; De Sanctis, Yoriko; Spiro, Theodore E.; Barnathan, Elliot S.; Raskob, Gary E.
Acutely ill medical patients are at risk of venous thromboembolism (VTE) and VTE-related mortality during hospitalization and posthospital discharge, but widespread adoption of extended thromboprophylaxis has not occurred. We analyzed a subpopulation within the MAGELLAN study of extended thromboprophylaxis with rivaroxaban to reevaluate the benefit risk profile. We identified 5 risk factors for major and fatal bleeding after a clinical analysis of the MAGELLAN study and analyzed efficacy and safety with these patients excluded (n = 1551). Risk factors included: active cancer, dual antiplatelet therapy at baseline, bronchiectasis/pulmonary cavitation, gastroduodenal ulcer, or bleeding within 3 months before randomization. We evaluated efficacy, safety, and benefit risk using clinically comparable endpoints in the subpopulation. At day 10, rivaroxaban was noninferior to enoxaparin (relative risk [RR] = 0.82, 95% confidence interval [CI] = 0.58-1.15) and at day 35 rivaroxaban was significantly better than enoxaparin/placebo (RR = 0.68, 95% CI = 0.53-0.88) in reducing VTE and VTE-related death. Major bleeding was reduced at day 10 (RR = 2.18, 95% CI = 1.07-4.44 vs 1.19, 95% CI = 0.54-2.65) and at day 35 (2.87, 95% CI = 1.60-5.15 vs 1.48, 95% CI = 0.77-2.84) for MAGELLAN versus this subpopulation, respectively. The benefit risk profile was favorable in this subpopulation treated for 35 days, with the number needed to treat ranging from 55 to 481 and number needed to harm from 455 to 1067 for all pairwise evaluations. Five exclusionary criteria defined a subpopulation of acutely ill medical patients with a positive benefit risk profile for in-hospital and extended thromboprophylaxis with rivaroxaban.